EFEKTIFITAS MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA PADI (PAPAN DIAGRAM) TERHADAP HASIL BELAJAR MATEMATIKA - Apriliani, Yunisatizzahroh; Nur Arif, Mohammad; Sutriyani, Wulan; Wakit, Ahmat (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
The aim of this research is to determine the effectiveness of implementing the problem based learning (PBM) learning model using diagram board media (PADI) on the learning outcomes of class V students at SDN 3 Menganti Jepara. This type of research is experimental research with One-Group Pretest-Posttest Design. The population in this study was all class V students at SDN 03 Menganti Jepara with a sample of 21 students. The data collection techniques used are tests, observation and documentation. Data analysis used includes (1) prerequisite tests, namely normality tests and homogeneity tests, (2) effectiveness tests. The results of this research show that learning with PBL assisted by PADI media on mathematics learning outcomes is effective because it fulfills three things, namely (1) the use of the PBL model with PADI media by teachers reaches the good category with a score of 3.62, (2) student activity in participating in learning using PBL with PADI media is in the good category with a score of 3.19, and (3) there is an increase in mathematics learning outcomes.